Budesonide and formoterol in a single inhaler improves asthma control compared with increasing the dose of corticosteroid in adults with mild-to-moderate asthma - Lalloo, UG; Malolepszy, J; Kozma, D; Krofta, K; Ankerst, Jaro ; 0000-0002-0829-9129; Johansen, B; Thomson, NC (Chest, 2003)
Background: We evaluated the efficacy and safety of low-dose budesonide/formoterol, 80 mug/4.5 mug, bid in a single inhaler (Symbicort Turbuhaler; AstraZeneca; Lund, Sweden) compared with an increased dose of budesonide, 200 mug bid, in adult patients with mild-to-moderate asthma not fully controlled on low doses of inhaled corticosteroid alone. Methods: All patients received budesonide, 100 jig bid, during a 2-week run-in period. At the end of the run-in phase, 467 patients with a mean FEV1 of 82% predicted received 12 weeks of treatment with budesonide/formoterol in a single inhaler or budesonide alone in a higher dose. Patients kept daily records of their morning and evening peak expiratory flow (PEF), nighttime and daytime symptom scores, and use of reliever medication. Results: The increase in mean morning PEF-the primary efficacy measure-was significantly higher for budesonide/formoterol compared with budesonide alone (16.5 L/min vs 7.3 L/min, p = 0.002). Similarly, evening PEF was significantly greater in the budesonide/formoterol group (p < 0.001). In addition, the percentage of symptom-free days and asthma-control days (p = 0.007 and p = 0.002, respectively) were significantly improved in the budesonide/formoterol group. Budesonide/formoterol decreased the relative risk of an asthma exacerbation by 26% (p = 0.02) compared with budesonide alone. Adverse events were comparable between the two treatment groups. Conclusion: This study shows that in adult patients whose mild-to-moderate asthma is not fully controlled on low doses of inhaled corticosteroids, single-inhaler therapy with budesonide and formoterol provides greater improvements in asthma control than increasing the maintenance dose of inhaled corticosteroid.
Keywords: formoterol; inhaled corticosteroids; long-acting; beta(2)-agonists; Symbicort; asthma; budesonide